Ecoremediation of aquatic ecosystems (on the river Ščavnica in the municipality of Razkrižje) - Vovk Korže, Ana (Journal for Geography, 2020)
Due to frequent floods of the river Ščavnica in the municipality of Razkrižje, the municipal administration in cooperation with local residents decided to prepare application and implement the project "Bridge", in which they constructed a bridge over the river with ecoremediation measures in the riverbed and along it. In the development vision, the municipality of Razkrižje supports sustainable measures and thus the connection of environmental, social and economic approaches. It is this aspect of how ecoremediations affects the sustainable development of the local environment that interested us in this paper. In the first part we presented the understanding of ecoremediations and their dimensions, then their implementation on the river Ščavnica in the municipality Razkrižje and the main result of this paper is the evaluation of synergistic effects of ecoremediations in connection with tourism, movement in nature,development of new activities (self-sufficiency, green jobs) and intergenerational integration.or a synthesis assessment of the effects of ecoremediations, we used the current knowledge from the literature and conducted an interview with the mayor of Razkrižje and the municipal administration and randomly selected locals. We found that such approaches could have an effective impact on reducing environmental damage, increasing biodiversity with social and economic effects, which we associate with the concept of green development.
Keywords: ecoremediations; municipality Razkrižje; Ščavnica; sustainability; flood